Internalization of Local Traditional Values in A Plurality Community: Interreligious Relations in Sawangan, Magelang - Setiyani, Wiwik; Effendi, Masitah; Yuldashov, Sodik Okbaevich (KARSA Journal of Social and Islamic Culture, 2022)
The Sawangan community is one of the references in building harmony between religious people. Local Traditions have made it a symbol of community identity as well as a unifying relationship between religions. This article will explain the local traditional values â€‹â€‹of the Sawangan community. The research method was carried out by in-depth interviews. Peter L. Berger’s theory becomes an analytical tool in finding the process of internalizing local traditions in a plural society. The object of the research was carried out at the Sawangan Magelang location. The research finding is that the diversity of the community can inspire because, from upstream to downstream, there are synergies in building communities through local traditions. Friction between communities can be addressed quickly and responsively. People get comfort in carrying out activities through various cultural arts activities. Various religious backgrounds are united in the frame of local traditions as well as become the glue between the people. Local traditions internalize in society to create a peaceful society that is tolerant of all religions and beliefs. The spirit of togetherness fosters empathy and sympathy to complement each other in their work so that local traditional values â€‹â€‹have internalized the Sawangan community.